Letter from Carl D. Duncan to Patricia Whiting, October 12, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Carl D. Duncan compliments Patricia Whiting on her treatment of other people. Highlighted in this letter is her treatment of foreign visitors and students.